The search for extra dimensions - Abel, S; March-Russell, J (2000)
Steven Abel and John March-Russell discuss whether three dimensions exist in the universe and how they can be detected. Explaining why the cosmological constant is so small has occupied cosmologists and particle physicists ever since Einstein first introduced it. Many proponents of the brane-world picture are tackling this problem again. A typical process might involve a proton and antiproton colliding to produce a single spray or jet of particles plus a graviton, which is emitted into the bulk. The particles that are confined to the brane also have Kaluza - Klein or higher string-excitation states, but for them the relevant scale is either the brane thickness or the new fundamental string scale. Both of these scales should correspond in energy to the new gravity scale of 1000 GeV or higher.